2008
DOI: 10.1016/j.jvs.2007.11.026
|View full text |Cite
|
Sign up to set email alerts
|

Prospective randomized efficacy of ultrasound-guided foam sclerotherapy compared with ultrasound-guided liquid sclerotherapy in the treatment of symptomatic venous malformations

Abstract: These findings suggest that UGFS could have greater promise compared with UGLS in the treatment of VMs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
106
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(109 citation statements)
references
References 21 publications
2
106
0
1
Order By: Relevance
“…Efficacy of foam sclerotherapy (FS) and liquid sclerotherapy (LS) has been investigated in a comparative non-RCT conducted by Yamaki et al 30 Under ultrasound guidance, 62 patients were injected with either foam or liquid to treat GSV incompetence. Occlusion of saphenous incompetence was achieved in 68% of foam-treated patients and 17.5% of liquid-treated patients after 12 months.…”
Section: Clinical Resultsmentioning
confidence: 99%
“…Efficacy of foam sclerotherapy (FS) and liquid sclerotherapy (LS) has been investigated in a comparative non-RCT conducted by Yamaki et al 30 Under ultrasound guidance, 62 patients were injected with either foam or liquid to treat GSV incompetence. Occlusion of saphenous incompetence was achieved in 68% of foam-treated patients and 17.5% of liquid-treated patients after 12 months.…”
Section: Clinical Resultsmentioning
confidence: 99%
“…In previous studies, STS has been associated with success rates of 43-84%, 52,[54][55][56] whereas polidocanol has similarly reported ranges of 45-84%. 57,58 Importantly, the definition of an adequate response as well as the lesion size, anatomical location and patient population is highly variable among previous studies, and, thus, it is difficult to ascertain the true efficacy of STS and polidocanol for VM treatment.…”
Section: Capillary Malformationsmentioning
confidence: 99%
“…However, the majority of complications with both STS and polidocanol are minor, with pain at the injection site and local skin necrosis being the most common 53,63,64 and likely related to tissue extravasation with damage of adjacent vessels at the injection site. 64,65 A recent study has shown greater efficacy with foamed vs liquid injection of polidocanol, 57 and new guidelines suggest both polidocanol and STS should be administered in foam form. 66 The use of foam instead of liquid allows greater volume coverage and increased surface area contact with the vessel endothelium, while also slowing flow through the lesion to maximize contact with the vessel.…”
Section: Capillary Malformationsmentioning
confidence: 99%
“…It has been faced with problems including dispersion of drug into surrounding tissue with significantly reduced therapeutic effect, or invasion of important tissues adjacent to the lesion such as nerves, salivary glands or vessels, which can lead to serious complications. Ultrasound guidance was first used by Yamaki (32)with VMs in the cervical-facial region by intralesional injection of absolute alcohol, and he researched this method in detail with reported advantages like prevention of intra-arterial injections (34,35).…”
Section: Discussionmentioning
confidence: 99%